Experimental and Computational Studies of Phenylene-Bridged Azaacenes as Affinity Materials for Sensing Using Quartz Crystal Microbalances - Prantl, Ephraim; Hahn, Sebastian; Bunz, Uwe H. F.; Waldvogel, Siegfried R. (Organic Materials, 2022)
Phenylene-bridged, TIPS-alkynylated azaacenes are excellent materials for selective gas sorption. In this study, we utilized 195 MHz high-fundamental-frequency quartz crystal microbalances, coated with cyclic azaacenes, and determined their affinity towards hazardous and narcotics-related compounds such as benzene, γ-butyrolactone (GBL) or safrole. Computational investigations by extended tight binding intermolecular force field allowed better understanding of the determined unique features. Remarkable selective affinities were found towards GBL and safrole – both dangerous compounds which can be abused as precursors for narcotics. With these systematic approaches, we were able to get a better insight into the selective adsorption and how to design better affinity materials
Keywords: affinity materials; quartz crystal microbalances; sensors; azaacene; trace analysis